2022
DOI: 10.21203/rs.3.rs-1688309/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Use of the Behaviour Change Wheel to design an intervention to improve the provision of mental wellbeing support within the audiology setting

Abstract: Objective: This study describes the development of an intervention to increase the frequency of audiologists’ asking about and providing information regarding mental wellbeing within adult audiology services.Design: The Behaviour Change Wheel (BCW), an eight-step systematic process, was followed to develop the intervention. Reports describing the first four steps are published elsewhere. This report describes the final four steps and details the intervention developed.Results: A multifaceted intervention was d… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…2; see Supplemental Data Six in Supplemental Digital Content, http://links.lww. com/EANDH/B262), which align with the barriers targeted by the intervention (Bennett et al 2023a; see Supplemental File One in Supplemental Digital Content, http://links.lww.com/ EANDH/B257); including for example, "audiologists require clinical resources to assist with (i) asking about wellbeing, (ii) providing information on the wellbeing impacts of hearing loss, and (iii) providing information on wellbeing treatment/management strategies," "audiologists need to develop confidence in their ability to ask about mental wellbeing and respond with empathy when clients describe their challenges," "Audiologists need reminders/prompts to help them remember to ask clients about mental wellbeing," and "audiologists need to feel responsible for (i) asking about mental wellbeing, (ii) providing information on the mental wellbeing impacts of hearing loss, and (iii) providing information on mental wellbeing treatment/management strategies. "…”
Section: Similarity Between Com-b Barriers At Preimplementation and T...mentioning
confidence: 95%
See 2 more Smart Citations
“…2; see Supplemental Data Six in Supplemental Digital Content, http://links.lww. com/EANDH/B262), which align with the barriers targeted by the intervention (Bennett et al 2023a; see Supplemental File One in Supplemental Digital Content, http://links.lww.com/ EANDH/B257); including for example, "audiologists require clinical resources to assist with (i) asking about wellbeing, (ii) providing information on the wellbeing impacts of hearing loss, and (iii) providing information on wellbeing treatment/management strategies," "audiologists need to develop confidence in their ability to ask about mental wellbeing and respond with empathy when clients describe their challenges," "Audiologists need reminders/prompts to help them remember to ask clients about mental wellbeing," and "audiologists need to feel responsible for (i) asking about mental wellbeing, (ii) providing information on the mental wellbeing impacts of hearing loss, and (iii) providing information on mental wellbeing treatment/management strategies. "…”
Section: Similarity Between Com-b Barriers At Preimplementation and T...mentioning
confidence: 95%
“…In developing the AIMER intervention, we first identified barriers and facilitators affecting HHCs ability to enact the three target behaviors through focus group discussion; these included factors identified across all three areas of the COM-B: capability, opportunity, and motivation (Nickbakht et al 2022;Bennett et al 2023b). Of the 93 factors identified, 19 were selected, and the AIMER intervention was systematically designed to target these 19 barriers (Bennett et al 2023a; see Supplemental File One in Supplemental Digital Content, http://links.lww.com/ EANDH/B257).…”
Section: Did the Intervention Work Via The Com-b Mechanisms We Predic...mentioning
confidence: 99%
See 1 more Smart Citation
“…139 The four key elements are as follows: Development (identifying the evidence base and theory); Feasibility/piloting (testing procedures, estimating recruitment/retention, calculating sample size); Evaluation (assessing clinicaland cost-effectiveness, understanding the change process); and Implementation (dissemination, monitoring, and long-term follow-up). This framework has guided some of our research, 15,115,140,141 and has been recently updated 142 to align with important aspects that have been introduced into research over the last decade. These include stakeholder engagement, 12,116,[143][144][145] identifying key uncertainties, 146,147 iterative refinement of the intervention, 15,116,144,145,148 and economic considerations.…”
Section: Implementation and Behavioral Science: From Research To Prac...mentioning
confidence: 99%
“…41 We recently used the BCW to develop an intervention targeting mental well-being support behaviors in hearing healthcare clinicians, the AIMER (Ask, Inform, Manage, Encourage, Refer). 141 This multifaceted intervention was developed to change hearing healthcare clinicians' behaviors relating to provision of mental well-being support to adults with hearing loss. A follow-up study evaluated the implementation of the AIMER, guided by the RE-AIM framework 160 providing a theoretical structure for the assessment of implementation pathways, and found that after completing the AIMER program, hearing healthcare clinicians were more likely to engage in the target behaviors.…”
Section: Implementation and Behavioral Science: From Research To Prac...mentioning
confidence: 99%